"Missed opportunities": Adults with visual impairments' reflections on the impact of physical education on current physical activity. (January 2019) - Yessick, Amanda; Haegele, Justin A
Research suggests that adults with visual impairments tend to participate in inadequate amounts of physical activity and are at high risk for developing health-related conditions. The most likely environment for youth with visual impairments to learn about physical activity is school-based physical education (PE) classes. However, little research exists examining the influence of PE on lifelong physical activity for those with visual impairments. Therefore, the purpose of this study was to explore the perspectives of adults with visual impairments toward the impact of PE on their current physical activity participation. Sixteen participants (7 males and 9 females) with visual impairments who attended integrated public schools and private schools participated in this study. Data were collected through semi-structured, audio-taped telephone interviews and reflective field notes. A semi-structured interview guide was used to ensure that the same lines of inquiry were pursued across participants. Member checking, peer debriefing, and communicative validity were utilized to support trustworthiness. An inductive analysis was used to interpret the data. Two key themes were revealed. The first theme, ineffectual PE experiences, described participants' beliefs that PE experiences had little impact on their current physical activity. The second theme, retrospective needs, revealed modifications the participants believed would have improved their PE experiences. One of the primary objectives of PE is to provide the tools needed for lifelong physical activity. Upon completion of the study, most participants indicated that they considered themselves to be physically active in adulthood. However, this was attributed to meaningful experiences outside of their respective school-based PE classes.